2019
DOI: 10.1177/0962280219884574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of structural equation modelling, item response theory and Rasch measurement theory-based methods for response shift detection at item level: A simulation study

Abstract: When assessing change in patient-reported outcomes, the meaning in patients’ self-evaluations of the target construct is likely to change over time. Therefore, methods evaluating longitudinal measurement non-invariance or response shift at item-level were proposed, based on structural equation modelling or on item response theory. Methods coming from Rasch measurement theory could also be valuable. The lack of evaluation of these approaches prevents determining the best strategy to adopt. A simulation study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…These good performances may be related to the Bonferroni correction applied in the two iterative steps (step C and step 3) following likelihood ratio tests and to the iterative steps themselves. This asset of ROSALI has already been shown in a previous simulation study [14]. In fact, if LRT wrongly concludes to the presence of recalibration or difference in item difficulties between groups at time 1, often no items will be identified in the following iterative step, hence, the wrong decision of LRT is corrected in the final model of ROSALI.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…These good performances may be related to the Bonferroni correction applied in the two iterative steps (step C and step 3) following likelihood ratio tests and to the iterative steps themselves. This asset of ROSALI has already been shown in a previous simulation study [14]. In fact, if LRT wrongly concludes to the presence of recalibration or difference in item difficulties between groups at time 1, often no items will be identified in the following iterative step, hence, the wrong decision of LRT is corrected in the final model of ROSALI.…”
Section: Discussionsupporting
confidence: 55%
“…HRQoL). They were compared recently [14] and the method based on Rasch Measurement Theory (RMT) models, called the RespOnse Shift ALgorithm at Item level (ROSALI) showed better performances compared to other methods for detecting and accounting for recalibration RS in the measurement of PRO change. However, in this version of ROSALI it is assumed that the majority of patients experiences RS the same way.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As these latent variable models allow to formally specify and estimate the measurement model between the target construct (as latent variable(s)) and the measure (e.g. the items) using a set of equations, a test verifying whether this set of equations can be assumed equivalent at each time of measurement can be seen as a formal test of the violation of the PCI [45][46][47]. Sébille et al's critical review of the literature also demonstrated that there are other response shift methods that also examine discrepancies between target change and observed change [12].…”
Section: Implications Of the Formal Definition And Its Application To Proms At Two Time Pointsmentioning
confidence: 99%
“…The remaining methods rely on various statistical methods. Within the framework of latent variable models, methods include Structural Equation Modeling (SEM) [13], Item Response Theory [33] and Rasch Measurement Theory [34]. Other frameworks not necessarily requiring modeling of latent variables encompass Relative Importance Analysis [35], Classification and Regression Tree [36], Random Forest Regression [37], and Mixed Models and Growth Mixture Models [38].…”
Section: Team 2: Operationalization and Response Shift Methodsmentioning
confidence: 99%